Impact of COVID-19 on primary care visits: lesson learnt from the early pandemic period - Sholahuddin Rhatomy; Thomas Edison Prasetyo (Journal of Community Empowerment for Health, 2020)
In Indonesia, primary healthcare facilities play important roles in disease control and prevention. Changes in healthcare seeking behavior during the COVID-19 pandemic, especially to primary care, might have impacts to the overall public health status. This comparative epidemiology study aimed to investigate the changes of healthcare seeking behavior in primary care settings during the early pandemic period. Weekly number of visits to a primary healthcare facility in Klaten, Indonesia was examined from the 1st week of 2018 –through the 25th week of 2020. The selected period affected early by COVID-19 in 2020 was defined (early pandemic period) and compared to the same corresponding period in 2019 (comparison period). The total number of patient visits, number of visits by age, gender, clinical decisions, patient status and diagnostic categories were obtained, compared and analyzed. Mean differences and prevalence ratio of a specific diagnostic category between the two periods were calculated. The lowest period was from weeks 14 – 21, 2020, which we identified as the early pandemic period. Comparing the early pandemic period to the comparison period, we found that there was 46.3% decrease of total number of visits. The decline was especially apparent for children aged 0-9 (71%), females (46%), registered patients (49%) and outpatients (48%). Most of diagnostic categories also saw declines. Unfortunately, patients with hypertension also saw notable decline in mean differences and prevalence ratio albeit not desirable. In conclusion, some declines in the number of visits were not desirable including decreasing hypertension visit. This trend might negatively impact public health status afterward. Proper countermeasures are needed to control the ongoing trend. Further studies regarding the impact of COVID-19 on treatment seeking behavior is needed to plan effective countermeasures.